Basalt rock fiber reinforcement - Tarya, Rida; Mehdi Sayyed, Mohd.; Satpute, Nikhil; Shaikh, Sameer; Pathan, Majead (International Journal of Recent Advances in Multidisciplinary Topics, 2021)
Basalt is one of the most common igneous rocks on the planet and is the only ingredient needed to make basalt fibers which in turn is converted into basalt rebars. Recent development in fiber production technology allows the making of basalt fibers which are made from basalt rock. Basalt bars commonly known as Basalt Fiber Reinforced Polymer (BFRP) is an innovative component, a new material, which can be used in construction and civil applications as an alternative material to steel rebar. This paper compares the test results of beams designed with steel rebar and basalt rebar using ETABS. As more testing is completed and more design aids become available, it will help engineers to include basalt rebars in projects. Its use will become more widely accepted.